Industrial Development and Social Toxins: A Review Article: Pembangunan Industri dan Racun Sosial: Sebuah Artikel Ulasan - Ali, Wasfi Dhahir Abid (Universitas Muhammadiyah Sidoarjo, 2024)
The Industrial Revolution brought about changes in society in many areas, economic and social, including ways of living, where industrialization dominated manual craft manufacturing, which changed the ways of living. Modern history is the process of transformation in the economy, and this change had positive and negative consequences. Some benefits of this revolution include faster rates of economic growth, lower costs, better quality, and more services for people. On the other hand, there are drawbacks, such as fewer job prospects and the potential for the gap between the rich and the poor to expand Highlights: Industrialization replaced manual labor, transforming society and ways of living. Benefits: economic growth, lower costs, better quality, increased services. Drawbacks: job loss, widened wealth gap, social inequalities. Keywords: Industrial Development, Social Toxins, Review.